Timing of Delivery in Intrahepatic Cholestasis of Pregnancy With Total Bile Acids 40–99 µmol/L: A Decision Analysis [39N]. (May 2020) - Frank, Zoe C.; Nienow-Birch, Mary N.; Lo, Jamie; Shaffer, Brian L.; Caughey, Aaron B.
Abstract : INTRODUCTION: Our study models the trade-off between preterm neonatal morbidity and stillbirth for women with intrahepatic cholestasis of pregnancy (ICP) with total bile acids (TBA) between 40 and 99 µmol/L in order to determine the optimal gestational age for delivery. METHODS: A decision analytic model was created to compare the outcomes of delivery at 33 through 40 weeks gestation in women with TBA between 40 and 99 µmol/L. Baseline morbidity and mortality risks were derived from the literature and adjusted where appropriate for peak TBA and administration of antenatal steroids. We assumed a population of 10, 000 women with ICP and calculated total quality-adjusted life years (QALYs) for each strategy, taking into account both maternal and neonatal perspectives. Univariate sensitivity analysis was performed for all variables to test the robustness of the model. RESULTS: In women with TBA between 40 and 99 µmol/L, delivery at 39 weeks maximized QALYs, resulting in 700.6 more QALYs but 5.3 more stillbirths than delivery at 36 weeks. Sensitivity analysis demonstrated that delivery at 38 weeks became optimal when the relative risk of stillbirth given TBA between 40 and 99 µmol/L rose from a baseline of 1.00 to 4.91. Monte Carlo analysis demonstrated that when variation was incorporated into the model, delivery at 39 weeks was optimal 38% of the time and delivery at 38 weeks 25% of the time. CONCLUSION: In women with ICP with TBA between 40 and 99 µmol/L, delivery between 38 and 39 weeks may be optimal.